Analisis Program Tazkiyatun Nafs pada Pesantren Mahasiswa Universitas Aisyiyah Bandung - Moh. Irsyad Junaidi; Nan Rahminawati; Ayi Sobarna (UNISBA Press, 2022)
Abstract. The Tazkiyatun Nafs program is a new program that has existed and was then repackaged. This program is carried out at the beginning of the lecture, namely during the new student period. The aims of the research are (1) to find the philosophical basis for the Tazkiyatun Nafs program at the Islamic boarding school of Aiysiyah University, Bandung. (2) To examine the ideological basis of the Tazkiyatun Nafs program at the Islamic boarding school of Aisyiyah University, Bandung. (3) Analyzing the design of the Tazkiyatun Nafs program related to the formulation of materials, methods, educators, facilities and infrastructure as well as assessment in Islamic boarding schools, Aisyiyah University, Bandung. This research is an empirical research using a qualitative descriptive approach. Data collection techniques in this study used the interview method and the study of documentation. This qualitative research uses theoretical and empirical activities presented in the form of narrative texts to explain clearly how the philosophical basis and ideological basis for the formation of the Tazkiyatun Nafs program at Aisyiyah University Bandung, designs related to the formulation of materials, methods, educators, facilities and infrastructure as well as assessment in reviewing Tazkiyatun Nafs program at the Aiysiyah University Islamic boarding school in Bandung. The results of this study are: (a) the philosophical basis for the formation of the Tazkiyatun Nafs program, which is a phenomenon that occurs in this era of globalization so that mankind can remain focused in life. (b) the ideological basis for the formation of the Tazkiyatun Nafs program is to want to carry out da'wah in stages, starting with self-improvement and making students have good morals by providing education and teaching through coaching in pesantren. (c) The design of the Tazkiyatun Nafs program at Aisyiyah University Bandung, namely first, the formulation of the material which is divided into 3 stages of Tazkiyatun Nafs 1,2 and 3. Second, the formulation of methods using classical and practical learning methods. third, the determination of presenters who are tailored to their respective expertise. Fourth, the facilities and infrastructure on campus already support the activities of student boarding schools. Fifth, the program assessment is carried out with several elements, namely cognitive aspects, affective aspects and psychomotor aspects. Abstrak. Program Tazkiyatun Nafs merupakan program baru yang pernah ada dan kemudian di kemas kembali. Program ini dilaksanakan pada awal perkuliahan yaitu saat masa mahasiwa baru. Tujuan dari penelitian adalah (1) Menemukan dasar filosofi terjadinya program Tazkiyatun Nafs di pesantren Universitas Aiysiyah Bandung. (2) Mengkaji dasar idiologis terjadinya program Tazkiyatun Nafs di pesantren Universitas Aisyiyah Bandung. (3) Menganalisis perancangan program Tazkiyatun Nafs terkait perumusan materi, metode, pendidik, sarana dan prasarana serta penilaian di pesantren Universitas Aisyiyah Bandung. Penelitian ini merupakan penelitian empiric dengan menggunakan pendekatan deskriptif kualitatif. Teknik pengumpulan data dalam penelitian ini menggunakan metode wawancara dan studi dokumentasi. Penelitian kualitatif ini menggunakan kegiatan teoritis dan empiris disajikan dalam bentuk teks yang bersifat naratif untuk memaparkan secara jelas bagaimana dasar filosofis dan dasar idiologis terbentuknya program Tazkiyatun Nafs di Universitas Aisyiyah Bandung, perancangan terkait perumusan materi, metode, pendidik, sarana dan prasarana serta penilaian dalam mengkaji program Tazkiyatun Nafs di pesantren Universitas Aiysiyah Bandung. Hasil dari penelitian ini yaitu: (a) landasan filosofis terbentuknya program Tazkiyatun Nafs yaitu fenomena yang terjadi pada zaman globalisasi ini agar umat manusia dapat tetap terarah dalam kehidupan. (b) landasan ideologis terbentuknya program Tazkiyatun Nafs yaitu ingin melakukan dakwah secara bertahap yang diawali dengan pembenahan diri dan menjadikan mahasiswa berakhlakul karimah dengan memberikan Pendidikan dan pengajaran melalui pembinaan di pesantren. (c) Perancangan program Tazkiyatun Nafs di Universitas Aisyiyah Bandung yakni pertama, perumusan materi yang terbagi dalam 3 tahap Tazkiyatun Nafs 1,2 dan 3. Kedua, perumusan metode dengan menggunakan metode pembelajaran klasikal dan praktikal. ketiga, penentuan pemateri yang disesuaikan dengan keahliannya masing-masing. Keempat, sarana dan prasarana yang terdapat di kampus sudah mendukung kegiatan pesantren mahasiswa. Kelima, penilaian program yang dilakukan dengan beberapa unsur yaitu aspek kognitif, aspek afektif dan aspek psikomotorik.